2008
DOI: 10.1108/03321640810836708
|View full text |Cite
|
Sign up to set email alerts
|

Computational methods for modeling of complex sources

Abstract: Purpose -The purpose of this study is to develop and compare two methods of determining the total field, including phase information, when only field amplitudes have been measured on a set of planes in the near field of a complex electromagnetic source. Design/methodology/approach -The first method is a gradient-based optimization algorithm, based on the adjoint fields. The second method employs an optimization algorithm based on the phase angle gradients of a functional. Findings -The first method, the adjoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…One can divide plane 1 into a square grid with the grid cell area ∆S. If the point in the middle of the square number p is represented byr p , the Cartesian components of the electric fieldĒ in any point r on the other measurement planes can be calculated [9] with the expressions…”
Section: The Phase Angle Gradient Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One can divide plane 1 into a square grid with the grid cell area ∆S. If the point in the middle of the square number p is represented byr p , the Cartesian components of the electric fieldĒ in any point r on the other measurement planes can be calculated [9] with the expressions…”
Section: The Phase Angle Gradient Methodsmentioning
confidence: 99%
“…However, if the operation frequency is significantly reduced to MHz or even nearly to DC, phase retrieval in the region of a few wavelengths separation can be much harder to achieve. In view of this, Johansson et al [9] have recently proposed another phase retrieval method known as the Phase Angle Gradient Method (PAGM). Preliminary results have demonstrated that the method is able to perform phase retrieval at 100 MHz [10].…”
Section: Introductionmentioning
confidence: 99%
“…One can divide plane 1 into a square grid with the grid cell area ∆S. If the point in the middle of the square number p is represented byr p , the Cartesian components of the electric fieldĒ in pointr can be calculated [3] with the expressions…”
Section: The Phase Angle Gradient Methodsmentioning
confidence: 99%
“…There are several applications where such modeling is useful. Some examples are near-field to far-field transformations [1], antenna diagnostics [2] and electromagnetic dosimetry [3]. Phase-retrieval methods are interesting, since measurements of both amplitude and phase generally are more complicated and require more expensive equipment than phaseless measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation